ANALISIS PERSEPSI PETANI TERHADAP USAHATANI PADI DI KABUPATEN SUKOHARJO - Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2005)
Farm development policy is focused on increasing level ofliving and income, and also food security. The main subject of farm development is farmer with all of their limitation. Because of their position as a main subject, there is importance to understand their perseption on this farm management, where their perseption can be a support or an obstacle. Furthermore, it will be base to make decisions of continuing the production, farmer wealth, national food security, and finally the succesful offarm development. The base research method is descriptive analysis by survei thecnique. Research location had been choosen by multistage sampling. They are Banaran Village at Grogol District and Karang Wuni Village at Weru District. Samples are choosen by stratified sampling in number of 54 respondents. The data had been taken by quisioner using interview to farmer, and observation. To tes the relation personal factor and farmer perception on rice farming management is used Spearman Rank Correlation Coefficient Test, with confident level 95 %. The result shows that must of farmers (59.3 %) have low perception on rice farming management. Farmer personal factors and farmer perception on rice farming management have no significant relation in significanty level 95 %.